Thermal cracking products and bio-oil production from microalgae Desmodesmus sp. - Gang, Li; Shunan, Xiang; Fang, Ji; Yuguang, Zhou; Zhigang, Huang (International Journal of Agricultural and Biological Engineering, 2017)
Qualitative and quantitative analyses of thermal cracking products from Desmodesmus sp. were performed based on pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) at different temperature regimes (350°C-750°C). After further analysis of a series of total ions chromatogram (TIC) and summarized, thermal cracking products of Desmodesmus sp. at different temperature regimes can be obtained, which mainly comprised of aliphatic hydrocarbons, nitrogen compounds, aromatic hydrocarbons, fatty acids, ketones, alcohols, aldehydes and furan compounds. Compared to bio-oil production at 650°C (32.07%), Desmodesmus sp. pyrolyzed at 750°C could produce the highest bio-oil content of 42.25%. However, higher temperature could lead to the formation of contaminants (nitrogen compounds and PAHs) more easily. Therefore, considering the higher content of bio-oil conversion and less pollutants generation, the optimum temperature for Desmodesmus sp. thermal cracking conversion was about 650°C.Keywords: microalgae, Desmodesmus sp., thermal cracking, bio-oil production, pyrolysisDOI: 10.25165/j.ijabe.20171004.3348Citation: Li G, Xiang S N, Ji F, Zhou Y G, Huang Z G. Thermal cracking products and bio-oil production from microalgae Desmodesmus sp. Int J Agric & Biol Eng, 2017; 10(4): 198–206.